FORMATION OF SPIRITUAL VALUES OF PERSONALITY: THEORETICAL ASPECT OF THE PROBLEM - Oronovskaya Л.Д. (Pedagogy of Higher and Secondary Education, 2022)
The article focuses on the notion of the category of the essence of spirituality as the system of values due to winch unique personal self is formed.